WOMEN ARE LESS INNOVATIVE IN BUSINESS, OR ARE THEY? A DESCRIPTIVE STUDY ON INNOVATIONS IN WOMENAND MEN-OWNED BUSINESSES - Stošić Panić, Danijela; Janković Milić, Vesna (Economic Annals, 2024)
Innovation studies do not generally focus on the innovator. Consequently, the role of gender in a firm’s innovation practice is out of the focus of research. In order to fill this research gap, the present study explores the intensity and the type of innovative practice of womenand men-owned businesses operating in production and service sectors in the USA. This descriptive study’s results show that women- and men-owned businesses differ in terms of their innovativeness while the nature of these differences is related to the business sector and to the way in which the innovations are operationalised. Womenowned businesses are more likely to introduce product/service innovations, both generally and by sector. On the other hand, women-owned businesses are found to be less innovative in terms of process improvements, in general and in the service sector. The existence and the nature of the femalemale innovation gap vary depending on the operationalisation of the innovation variable as well. The paper includes the gender perspective in examining innovation, thus tackling the under-researched profile of the innovator. Moreover, it examines the wider context of innovations by including marginalised forms of innovations, such as incremental and process innovations, and it covers a range of industries which are usually neglected in innovation studies.